Personal Life of Medical Journal Editor: Artificial Intelligence as almost First Author may come to Rescue - Gupta, Deepak (Indian Journal of Community Health, 2023)
Utopic or dystopic future is on the horizon unless it is already here. Maybe it is utopic for medical journal editors if artificial intelligence (AI) is writing medical research papers submitted to medical journals because in due course of time, AI may evolve to become AI editors and AI peers relieving humans from burning the midnight oil to run medical journals as medical journal editors while seeking human peers for review of submitted articles before editing and publishing as many peer-reviewed articles as humanely and appropriately possible.